Child abuse potential in mothers with early life maltreatment, borderline personality disorder and depression. (24th May 2018) - Dittrich, Katja; Boedeker, Katja; Kluczniok, Dorothea; Jaite, Charlotte; Hindi Attar, Catherine; Fuehrer, Daniel; Herpertz, Sabine C.; Brunner, Romuald; Winter, Sibylle Maria; Heinz, Andreas; Roepke, Stefan; Heim, Christine; et al.
Abstract : Background: Early life maltreatment (ELM), borderline personality disorder (BPD) and major depressive disorder (MDD) have been shown to increase the potential of abuse. Emotion regulation is an identified mediator for the association of ELM and BPD with abuse potential. Until now, there has been no study to account for the co-occurrence of these risk factors in one analysis, although BPD and MDD are known as common sequelae of ELM. This is paired with a lack of studies investigating the effects of abuse potential on child well-being. Aims: Our study aims at (a) disentangling the effects of maternal ELM, MDD and BPD on abuse potential; (b) exploring the role of emotion regulation as a mediator; and (c) testing for intergenerational effects of abuse potential on child psychopathology. Method: The research design included 114 mothers with/without ELM, BPD and MDD in remission and their children, all of which were between 5 and 12 years of age. A path analysis was conducted to investigate the multiple associations between our variables. Results: ELM, MDD and BPD were all associated with abuse potential, with emotion regulation acting as a mediator for BPD and MDD. Furthermore, an elevated abuse potential was related to higher psychopathology in the child. Conclusions: History of ELM as well as the common sequelae, BPD and MDD, pose risks for child abuse. Our findings suggest improvement of emotion regulation as a potential target for intervention programs. These programs should also aim at non-substantiated cases because even an elevated abuse potential affected child mental health. Declaration of interest: None.